The Relationship between Body Mass Index and Histomolecular Classification of Breast Cancer - عبدالله نادر; عاقل سامر; وطفه زينه (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Increased body mass index (BMI) has been associated with the risk of developing breast cancer but the association based on molecular subtype remains conflicting. Aim: Our main objective of this research was to analyze the relation between BMI and various molecular subtypes of breast cancer stratified with patient’s age. Materials and Methods: This was a retrospective study conducted at Oncology Department. The study enrolled a total of 680 breast cancer patients (from 2012 to 2019). All patients’ BMI at the time of initial diagnosis and tumor demographics were recorded. BMI was stratified into 3 groups as normal-weighted (BMI <25 kg/m2), over-weighted (BMI=25 - 29.9 kg/m2), and obese (BMI ≥ 30 kg/m2). Immunohistochemical classification of the tumors was categorized into 5 groups as follows; luminal-A, luminal-B (Her2 like), luminal-B (Her2 negative), Her2 overexpression, and triple negative. Distribution of Immunohistochemical subtypes and tumor characteristics analysis were evaluated according to the BMI groups in both age groups (≤ 50 years and > 50 years). Results: Mean BMI of patients ≤ 50 years and patients > 50 years was 27.05 (kg/m2) and 30.06 (kg/m2), respectively (P < 0.0001). Patients > 50 years were more obese at diagnosis (P < 0.0001). Triple-negative subtype was significantly more frequent in obese patients ≤ 50 years compared to other subtypes (P = 0.049). Additionally, obese patients ≤ 50 years had less common luminal-A subtype (P = 0.024). Conclusion: Our data indicated that there is an association between BMI and breast cancer indicating a decreased incidence for luminal-A subtype and increased incidence for triple negative subtype among obese patients ≤ 50 years. However, this significance was not found in patients > 50 years.